Communication training program for market clerks: A case study of aphasia with agrammatism - Terradillos, Estíbaliz; Simón , Teresa; López-Higes, Ramón (Revista de Investigación en Logopedia, 2023)
The communicative competence of conversational partners may influence the social participation of a person with aphasia (PWA). This study examines the effects of an unfamiliar conversational partner training program on a PWA within a natural environment through an interaction-based approach. An agrammatic PWA was videotaped in six shopping situations within a marketplace before and after training was provided to three volunteer clerks (I1, I2 and I3) with no prior knowledge of aphasia. Using conversational analysis, nine communicative behaviors were identified in conversational partners and the interactions were scored using functional scales. There is a typical informal structure, but with context-dependent individual and inter-interaction variations. After training, qualitative changes in the frequency of use of nonverbal strategies were observed in all clerks. Likewise, I2 and I3 incorporated the retaking strategy and semantic facilitation, respectively. The results also show significant differences in the communicative competence of clerks, both overall and individually. Similarly, that subject with aphasia improves conversational engagement levels in both interactional and transactional acts, initiating new topics in all three interactions. This type of intervention requires time, knowledge of the context and the organization. The analysis of interactions with unfamiliar people during the shopping activity can guide speech-language pathologists on relevant aspects of intervention aimed at supporting the social participation of patients with aphasia.
Keywords: Aphasia; Social participation; interaction; conversation analysis; conversational partner training; communication strategies